Building Independent and Creative Characters: Entrepreneurship Programme in the Project of Strengthening Pancasila Learner Profile in Elementary School - Siti Zulaiha; Ranti Agustini (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research is based on the background that every school is required to implement the Merdeka curriculum including SDIT Juara, in order to succeed the implementation of the curriculum there is a P5 programme in the form of an Entrepreneurship programme. The purpose of this study is to describe 1) Implementation of P5 in the Entrepreneurship programme, 2) supporting and inhibiting factors in implementing P5 in the Entrepreneurship programme. This research is descriptive qualitative research, the subjects of this research are class I and IV teachers, curriculum vice principal, principal, students. Data collection methods are observation, interview and documentation. Data analysis with steps; data reduction, data presentation and data verification. Test data credibility by triangulating sources and techniques. The results of this study are: 1) The implementation of P5 is carried out with a team of facilitators, organising dimensions and time allocations which are carried out once a week on Saturdays, as well as project modules as a reference in project activities. The Pancasila Student Profile Strengthening Project (P5) is implemented in 6 dimensions. P5 has three stages, namely the implementation, planning and evaluation stages. 2) Supporting factors involved are good facilities and infrastructure, enthusiasm of teachers and school residents as well as support from the surrounding environment, cooperation between teachers and and the budget. While the inhibiting factors are the new curriculum, lack of monitoring and differences in student characteristics.